Evaluation 99mTc and 123I quantification using SPECT/CT - Mongane, Modisenyane Simon (University of the Free State, 2015)
A review of Single Photon Emission Tomography (SPECT) quantification shows that different protocols and phantoms are available to evaluate SPECT quantification accuracy. This study was necessitated by the lack of standardized protocols and the widespread use of a variety of non-standard phantoms. The aim of this work was to evaluate the influence of the geometry of a radionuclide distribution on SPECT quantification accuracy for 99mTc and 123I isotopes in an abdominal phantom. In order to achieve the aim, the following steps were taken: The preparatory phase of the study was to design and construct an abdominal phantom, verify the accuracy of the attenuation coefficients obtained with the Computed Tomography (CT) scanner, determine the accuracy of the source calibrator used in this study and then obtain a calibration factor in order to convert image counts to activity. During the quantification phase SPECT data were acquired, the influence of not applying scatter correction explicitly was evaluated and the final quantification was performed using the proposed standard clinical reconstruction protocols. The influence of different tumour sizes and locations in the abdominal phantom relative to a high uptake organ on the quantification accuracy was evaluated. Finally, parameters in the Ordered Subset Expectation Maximization (OSEM) reconstruction protocol were altered in order to investigate the influence of number of subsets and iterations on the quantified data. The non-standard Density Phantom with five different compounds was used for the verification of the 99mTc and 123I attenuation coefficients. The percentage difference between the measured and theoretical attenuation coefficients values were < 3%, except for Polystyrene (85% and 65% respectively). The SPECT calibration factor was determined for both 99mTc (11.0 ± 1.3 cpm/kBq) and 123I (10.8 ± 0.3 cpm/kBq) using the Cylindrical Phantom. The in-house built Abdominal Phantom was used to evaluate the tumour activity quantification accuracy. The quantification accuracy of 99mTc and 123I was found to change significantly (p < 0.05) as a function of tumour size after corrections for “spill out” counts due to the partial volume effect, scatter and attenuation were applied. On the other hand, there was no significant difference in the quantification accuracy (p > 0.05) for each tumour at different tumour-liver distances when appropriate scatter and attenuation corrections were applied. The influence of OSEM parameters showed no dependence on the tumour-liver distance and no significant difference (p > 0.05) between quantification with background activity as compared to no background activity. In conclusion, the study showed that the quantification accuracy for 99mTc and 123I was comparable to other published studies. It was found that the tumour quantification accuracy is not influenced by proximity of high uptake organs when appropriate correction factors were applied. Tumour size influenced the accuracy of SPECT quantification for both radionuclides. The results of this study also showed that at least 128 Maximum Likelihood Expectation Maximization (MLEM) equivalent iterations were needed during iterative reconstruction to achieve convergence and consistent SPECT quantification accuracy. Finally, it is recommended that the evaluated quantification protocol may be used in our nuclear medicine clinic for 99mTc and 123I quantification.

‘n Oorsig van Gerekenariseerde Enkel Foton Emissie Tomografie (GEFET) kwantifisering wys dat verskillende protokolle en fantome beskikbaar is om die akkuraatheid van GEFET kwantifisering mee te evalueer. Hierdie studie was genoodsaak deur ‘n tekort aan gestandardiseerde protokolle en die algemene gebruik van ‘n verskeidenheid van nie-standaard fantome. Die doel van hierdie studie was om die invloed van die geometrie van radionuklied verspreiding vir GEFET kwantifisering akkuraatheid te evalueer vir 99mTc en 123I radionukliede in ‘n abdominale fantoom. Om hierdie doel te bereik is die volgende stappe gevolg: Die voorbereidingsfase van hierdie studie was die ontwerp en konstruksie van ‘n abdominale fantoom, die verifiëring van die akkuraatheid van die attenuasie koeffisiënte wat verkry is met ‘n Rekenaar Tomografie skandeerder, bepaling van die akkuraatheid van die bronkalibreerder wat in hierdie studie gebruik is en die verkryging van ‘n kalibrasiefaktor om beeldtellings om te skakel na aktiwiteit. Gedurende die kwantifiseringsfase is GEFET data versamel, die uitwerking van geen verstrooiïngskorreksie was geëvalueer en die finale kwantifisering was uitgevoer deur gebruik te maak van die voorgestelde standaard kliniese rekonstruksie protokolle. Die invloed van verskillende tumor groottes en posisies in die abdominale fantoom relatief tot ‘n orgaan met hoë radioaktiewe opname op die akkuraatheid van die kwantifisering was ook geëvalueer. Laastens was parameters in die OSEM (“Ordered Subset Expectation Maximization”) rekonstruksie protokol verander om die invloed van verskillende aantal substelle en iterasies op die gekwantifiseerde data te ondersoek. Die nie-standaard Digtheid Fantoom met vyf verskillende digtheid samestellings was gebruik vir die verifikasie van die 99mTc en 123I attenuasie koeffisiënte. Die persentasie verskille tussen die gemete en teoretiese attenuasie koeffisiënt waardes was < 3%, behalwe vir Polystyrene (85% en 65% onderskeidelik). Die GEFET kalibrasie faktor was bepaal vir beide 99mTc (11.0 ± 1.3 cpm/kBq) en 123I (10.8 ± 0.3 cpm/kBq) deur die Silindriese Fantoom te gebruik. Die inhuis vervaardigde Abdominale Fantoom was gebruik om die akkuraatheid van die tumor aktiwiteit kwantifisering te evalueer. Die kwantifiseringsakkuraatheid van 99mTc en 123I het betekenisvol verskil (p < 0.05) as ‘n funksie van tumor grootte na die korreksies vir “misplaasde” tellings as gevolg van die parsiële volume effek, , verstrooiïng en attenuasie aangebring is. Daarteenoor was daar geen betekenisvolle verskil in die kwantifiseringsakkuraatheid (p > 0.05) vir elke tumor by die verskillende tumor-lewer afstande wanneer die gepaste verstrooiing en attenuasie korreksies toegepas was nie. Die invloed van OSEM parameters het geen afhanklikheid van tumor-lewer afstande getoon nie en geen betekenisvolle verskil (p > 0.05) tussen kwantifisering met agtergrond aktiwiteit in vergelyking met geen agtergrond aktiwiteit nie. Ter samevatting het hierdie studie aangetoon dat die kwantifiseringsakkuraatheid vir 99mTc en 123I vergelykbaar was met ander gepubliseerde studies. Dit is gevind dat tumor kwantifiseringsakkuraatheid nie beïnvloed word deur die nabyheid van hoë opname organe nie, mits die nodige korreksie faktore toegepas word. Tumor grootte beïnvloed die akkuraatheid van GEFET kwantifisering vir beide radionukliede. Die resultate van hierdie studie het ook aangetoon dat ten minste 128 MLEM (“Maximum Likelihood Expectation Maximization”) ekwivalente iterasies nodig was gedurende iteratiewe rekonstruksie om konvergensie en bestendige GEFET kwantifisering akkuraatheid te behaal. Laastens word dit aanbeveel dat die geëvalueerde kwantifiseringsprotokol gebruik mag word in ons kerngeneeskunde kliniek vir 99mTc en123I GEFET kwantifisering.
Dissertation (M.Med.Sc. (Medical Physics))--University of the Free State, 2015
Keywords: Single photon emission computed tomography; Quantification; Ordered subset expectation maximisation; Computed tomography; Tomography emission